Frequency of Subacute Stent Thrombosis (SAT) in Patients Presenting with Acute Coronary Syndrome Undergoing Percutaneous Coronary Intervention (PCI) - Ali, Khurshid; Abbasi, Muhammad Amad; Zafar, Kashif; Abid, Imran; Iqbal, Asim; Ghaffar, Shakir; Ahmed, Bilal; Kamran, Javeria; Azad, Naseem; Sana, Ayesha (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess the rate of occurrence of sub-acute Stent Thrombosis (SAT) after primary PCI in the patients presented with the acute coronary syndrome.Study Design: Retrospective cross-sectional study.Place and Duration of Study: At Tertiary Cardiac Care Center of Lahore Pakistan, from Jul 2019 to Jun 2021.Methodology: The retrospective demographical and angiographic data of the admitted patients who underwent PCI for ACS,was gathered from the Hospital Registry of a tertiary cardiac care center of Lahore. The sampling technique was nonprobability consecutive sampling, and all the data was analyzed using SPSS 20.0 and continuous data was presented as Mean±SD and frequencies & percentages for categorical variables. Chi square test (CI=95%, α=5%) was used to find the association of SAT with predisposing factors. p-value < 0.05 was taken as statistically significant.Results: Out of (n=551) patient underwent PPCI, the stent thrombosis was observed to occur in 29(5.2 %), among which 4.9 % were subacute stent thrombosis. The predisposing factors of sub-acute stent thrombosis were Diabetes Mellitus, ACS, smaller vessel size, presence of bifurcation lesion, under sizing of the stent and edge dissection and were in significant association with SAT (p < 0.05).Conclusion: Our study reveals that subacute stent thrombosis is an event with a comparatively higher frequency in patients who go through primary PCI for acute coronary syndrome, demonstrating a frequency of 4.9% and a mortality rate of 74% within 30 days of the procedure.